Kota dan masyarakat Jakarta : dari kota tradisional ke kota kolonial (abad XVI-XVIII) - Haris, Thawaluddin (Jakarta : Wedatama Widya Sastra, 2007)
History of Jakarta, Indonesia, from traditional to colonial town, XVI to XVIII century
Keywords: Jakarta (Indonesia) -- Social life and customs; Jakarta (Indonesia) -- Social conditions; Jakarta (Indonesia) -- History